(X+5)(x+5)-49=0

Simple and best practice solution for (X+5)(x+5)-49=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (X+5)(x+5)-49=0 equation:


Simplifying
(X + 5)(x + 5) + -49 = 0

Reorder the terms:
(5 + X)(x + 5) + -49 = 0

Reorder the terms:
(5 + X)(5 + x) + -49 = 0

Multiply (5 + X) * (5 + x)
(5(5 + x) + X(5 + x)) + -49 = 0
((5 * 5 + x * 5) + X(5 + x)) + -49 = 0
((25 + 5x) + X(5 + x)) + -49 = 0
(25 + 5x + (5 * X + x * X)) + -49 = 0
(25 + 5x + (5X + xX)) + -49 = 0

Reorder the terms:
(25 + 5X + 5x + xX) + -49 = 0
(25 + 5X + 5x + xX) + -49 = 0

Reorder the terms:
25 + -49 + 5X + 5x + xX = 0

Combine like terms: 25 + -49 = -24
-24 + 5X + 5x + xX = 0

Solving
-24 + 5X + 5x + xX = 0

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '24' to each side of the equation.
-24 + 5X + 5x + 24 + xX = 0 + 24

Reorder the terms:
-24 + 24 + 5X + 5x + xX = 0 + 24

Combine like terms: -24 + 24 = 0
0 + 5X + 5x + xX = 0 + 24
5X + 5x + xX = 0 + 24

Combine like terms: 0 + 24 = 24
5X + 5x + xX = 24

Add '-5x' to each side of the equation.
5X + 5x + -5x + xX = 24 + -5x

Combine like terms: 5x + -5x = 0
5X + 0 + xX = 24 + -5x
5X + xX = 24 + -5x

Reorder the terms:
-24 + 5X + 5x + xX = 24 + -5x + -24 + 5x

Reorder the terms:
-24 + 5X + 5x + xX = 24 + -24 + -5x + 5x

Combine like terms: 24 + -24 = 0
-24 + 5X + 5x + xX = 0 + -5x + 5x
-24 + 5X + 5x + xX = -5x + 5x

Combine like terms: -5x + 5x = 0
-24 + 5X + 5x + xX = 0

The solution to this equation could not be determined.

See similar equations:

| -12=w+18 | | 5z-18-z+2= | | 10=(2*6)-8 | | 2x-3x-10=-9 | | B-2b=b+4b+2 | | 3(y-4)= | | 4x+8/4-2=x | | 2x^2-4x/x-2 | | 8+7x+4x=63 | | x+6=x.4 | | 99x+65=-4x | | z(4x^10y^11z^8)= | | 7+3C=-7 | | .25n=2n-21 | | 5(2x-12)+21=2x+21 | | w=4x(y-5) | | 210(-3)= | | 2(3+x)=20+3x | | 9y+2=11y+8 | | z(16xy^3z^3)= | | e^4y-ln(y^2+3)=2x | | Yy-2=y+1y-5 | | 27x^2-54x+2805=0 | | x+8=-2-2+5x | | 2w-4=2 | | 2w-4= | | k=11+9-8+99 | | -6x+8=6x+8 | | 17+b= | | log(5*3)= | | G(f(3))+g(g(8))= | | 5a-5+4a+8=10a+40 |

Equations solver categories